PERCERAIAN NIKAH DI BAWAH UMUR DAN PENGARUHNYA TERHADAP PENGASUHAN ANAK DI KECAMATAN MANDUAMMAS KABUPATEN TAPANULI TENGAH - Abu Bakar, Erni Yanti Tinambunan (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2022)
The age of marriage in Indonesia has been regulated by law, precisely in Article 7 paragraph 1 of Law Number 1 of 1974 which reads, "Marriage is only permitted if the man reaches the age of 19 (nineteen) years and the woman has reached the age of 19 (nineteen) years. age of 16 (sixteen) years. And as has been stipulated regarding amendments to the 1974 Marriage Law with Law Number 16 of 2019, the Law states that the marriage age for both men and women is 19 years. This research is entitled "Minor Marriage Divorce and Its Effect on Child Care", this study has a problem formulation, namely (1). What are the factors that cause underage marriage divorce in Manduamas District, Central Tapanuli Regency, (2). How is the impact and influence of divorce from underage marriage on child care in Manduamas District, Central Tapanuli Regency, and (3). How is the review of Islamic law on child care as a result of underage marriage divorce. While the objectives of this study are (1). To describe what are the factors that cause underage marriage divorce in Manduamas District, Central Tapanuli Regency, (2). To describe the impact and influence of divorce from underage marriage on child care in Manduamas District, Central Tapanuli Regency, (3). To describe a review of Islamic law on child care as a result of underage marriage. This study uses a qualitative approach and this type of research is descriptive research. The data sources used in this study are primary data sources and secondary data sources. Data was collected by means of interviews, documentation studies and observations. Based on the results of the study, it shows that the factors that cause divorce from underage marriages are the frequent occurrence of domestic violence and the presence of a third person in the respondent's household. The impact and influence of divorce from underage marriage on child care in Manduamas sub-district, namely: When a divorce occurs, custody of the child falls to the mother. After a divorce, the most impactful and influential thing when raising children is in terms of financing the child's life, and children's education. A review of Islamic law on child care as a result of underage marriage divorce that the most entitled to take care of children after divorce is the mother.